Melting in a vertical pipe due to asymmetric heating. (June 2020) - Nimrodi, Yonatan; Kozak, Yoram; Portnikov, Dmitry; Ziskind, Gennady
Abstract: This work deals with a study of asymmetric melting in a vertical stainless steel pipe. The pipe is filled with a phase change material and heated asymmetrically by a resistive heater attached to a part of its circumference along its entire height. The pipe is exposed to natural or forced convection external conditions. The experimental results include melt fraction that gives an accurate quantitative measure of the melting progress, obtained by measurements of the solid shape at different times. Also, infrared measurements of the outer surface of the pipe are presented. The experimental results constitute a reliable reference to a three-dimensional numerical model built using a commercial software. The modeling of system geometry and boundary conditions is explained. The numerical results include solid shapes during melting, temperature distribution, melt fraction and fluid velocity distribution. In a qualitative comparison of solid shapes, the experimental and numerical findings are in good agreement. The numerical results reveal details of the flow and heat transfer during melting. Graphical abstract: Image 1 Highlights: Asymmetric melting in a vertical stainless steel pipe is investigated. Experimental results include melt fraction obtained by measurements of the solid shape. Infrared measurements of the outer surface of the pipe are presented. Three-dimensional numerical model is built using a commercial software. The numerical results reveal details of the flow and heat transfer during melting.